Irony, Denial and Retrospective Loss in Bruno Major’s Songs - Figo Alfandi; Udur Delima Sibatuara (BLESS, 2026)
This study analyses the use of emotional and temporal irony, as well as imagery, in expressing denial and retrospective loss in the songs We Were Never Really Friends and Trajectories by Bruno Major. The research explores how irony creates contradictions between expectation and reality, and how imagery contributes to the emotional construction of loss and self-protection in the lyrics. The study aims to answer two research questions: In what ways do emotional and temporal irony reflect denial and retrospective loss in the songs? How does imagery contribute to the expression of denial and retrospective loss? This research employs a qualitative descriptive method. The data were collected by listening to the songs, transcribing the lyrics, and identifying lines containing emotional irony, temporal irony, and types of imagery, including concealment, auditory, visual, and physical imagery. The analysis was conducted by interpreting the lyrics based on theories of irony, denial, retrospective loss, and imagery. The findings reveal that temporal irony reflects the gap between past expectations and present reality, highlighting the speaker’s inability to accept relational separation. Emotional irony functions as a defense mechanism, masking emotional pain through contradictory expressions of acceptance and happiness. Furthermore, imagery enriches the lyrical meaning by symbolically dramatizing emotional suppression, longing, and memory reconstruction. The study concludes that irony and imagery work together to construct denial as a psychological defense and to shape retrospective loss as an emotionally reconstructed experience.